2009
DOI: 10.1038/jhh.2009.53
|View full text |Cite
|
Sign up to set email alerts
|

Circadian blood pressure and heart rate characteristics in haemorrhagic vs ischaemic stroke in Chinese people

Abstract: To compare the circadian variation of blood pressure (BP) between patients with intra-cerebral haemorrhage (ICH) and with cerebral infarction (CI), around-the-clock BP measurements were obtained from 89 hypertensive patients with ICH, from 63 patients with CI and from 16 normotensive volunteers. The single and populationmean cosinor yielded individual and group estimates of the MESOR (Midline Estimating Statistic Of Rhythm, a rhythm-adjusted mean value), circadian double amplitude and acrophase (measures of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…lacunar, thrombotic, embolic stroke. Circadian and circaseptan variations in the onset in stroke incidence have been reported by Halberg group in relation to circadian hyperamplitude tension [91,92]. In acute myocardial ischemia, the time of onset is easily determined [93,94] corresponding with the onset of thoracic pain and does not occur when the patient with ischemic stroke is discovered on awakening; the onset may have occurred at any time during sleep.…”
Section: Circadian Periodicity and Strokementioning
confidence: 99%
See 1 more Smart Citation
“…lacunar, thrombotic, embolic stroke. Circadian and circaseptan variations in the onset in stroke incidence have been reported by Halberg group in relation to circadian hyperamplitude tension [91,92]. In acute myocardial ischemia, the time of onset is easily determined [93,94] corresponding with the onset of thoracic pain and does not occur when the patient with ischemic stroke is discovered on awakening; the onset may have occurred at any time during sleep.…”
Section: Circadian Periodicity and Strokementioning
confidence: 99%
“…It is possible that eating dinner rich in protective nutrients that can modulate vascular biology and increase blood pressure may be protective in the morning against stroke. There is evidence that CHAT carries several fold greater risk of stroke than MESOR hypertension [91,92]. A recent study showed that increased intake of alphalinolenic acid by eating 50-10g/day of walnuts can inhibit CHAT and decrease blood pressures.…”
Section: Controversies In the Circadian Periodicity Of Strokementioning
confidence: 99%
“…Animal studies have shown a rapid increase in mean heart rate in post-malignant stroke mice, with an increase of about 100 bpm from pre-malignant stroke [27]. Mean heart rate was signi cantly higher in patients with stroke than in those with normotensive, and heart rate variability was greater in patients with ischemic stroke than in patients with hemorrhagic stroke [29]. At present, no evidence has been found to explain the increase in mortality with increased Amplitude of heart rate in stroke and critically ill patients, which requires further investigation.…”
Section: Discussionmentioning
confidence: 99%